Compare Unidimensional & Multidimensional Rasch Model for Test with Multidimensional Construct and Items Local Dependence - Ali Hasmy (Journal of Education and Learning (EduLearn), 2014)
Test in education, generally, constructed based on multi contents.  If every contents viewed as a dimension, hence the test also have multi-dimension too, so that the analysis must be done with the multidimensional model. In reality at some selected tests, we can see that dependence exist between items in different contents.  Dependence as referred, make assumption about multidimensional test is not valid anymore so that gives us the opportunity to apply unidimensional models in its analysis, including by using Rasch Model.  This matter motivated me to do write this paper with aim to: get Unidimensional Rasch Model based on logistics function, get the item parameter estimation and testee parameter estimation together using the Joint Maximum Likelihood Method, and prove that Unidimensional Rasch Model is the better choice than Multidimensional Rasch Model in condition like this.